2016
DOI: 10.1128/iai.00324-16
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Evolution of Yersinia Leucine-Rich Repeat Proteins

Abstract: c Leucine-rich repeat (LRR) proteins are widely distributed in bacteria, playing important roles in various protein-protein interaction processes. In Yersinia, the well-characterized type III secreted effector YopM also belongs to the LRR protein family and is encoded by virulence plasmids. However, little has been known about other LRR members encoded by Yersinia genomes or their evolution. In this study, the Yersinia LRR proteins were comprehensively screened, categorized, and compared. The LRR proteins enco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…(poly C tracts) and Mycoplasmataceae (dinucleotide tracts) are represented, which is not surprising given the prevalence of these types of repeats in these organisms, 49 with many R-M systems in Mycoplasmas previously identified as containing SSRs. However, the resulting amino acid repeats they encode may have important functional implications, as seen with other amino acid repeat containing proteins such as the RTX family of toxins produced by Gram-negative bacteria, 54 Leucine Rich Repeat (LRP) proteins, 55,56 and HsdS proteins. 52 We also identify a number of phase-variable hsdR genes in unusual or emerging pathogens such as EleORF768 from Eggerthella lenta, an anaerobic Gram-positive bacilli associated with abdominal sepsis, and Slu143ORF9045 from Staphylococcus lugdunensis, a member of the Staphylococci that has been known to cause septic arthritis.…”
Section: Many Bacteria Contain An Hsdr Gene Containing Short Ssr Trmentioning
confidence: 99%
“…(poly C tracts) and Mycoplasmataceae (dinucleotide tracts) are represented, which is not surprising given the prevalence of these types of repeats in these organisms, 49 with many R-M systems in Mycoplasmas previously identified as containing SSRs. However, the resulting amino acid repeats they encode may have important functional implications, as seen with other amino acid repeat containing proteins such as the RTX family of toxins produced by Gram-negative bacteria, 54 Leucine Rich Repeat (LRP) proteins, 55,56 and HsdS proteins. 52 We also identify a number of phase-variable hsdR genes in unusual or emerging pathogens such as EleORF768 from Eggerthella lenta, an anaerobic Gram-positive bacilli associated with abdominal sepsis, and Slu143ORF9045 from Staphylococcus lugdunensis, a member of the Staphylococci that has been known to cause septic arthritis.…”
Section: Many Bacteria Contain An Hsdr Gene Containing Short Ssr Trmentioning
confidence: 99%
“…This has prompted the development of effector prediction algorithms that focus on shared features of T3SEs, which includes amino acid biases that characterize the secretion and translocation signal (Arnold et al, 2009;Samudrala et al, 2009;Wang et al, 2011). Despite this, homology remains an effective way to catalog existing T3SE diversity, and to find potentially new distantly homologous effectors in newly sequenced genomes (Hu et al, 2016). As T3SEs are categorized, families delimited and T3SE distribution established, combinatorial T3SE prediction strategies can be developed that amalgamate sequence similarity as well as the associations of particular T3SEs with specific T3SSs.…”
Section: Introductionmentioning
confidence: 99%
“…Selection pressures based on bacteriophage binding have been observed in the past (34,35) and we hypothesize that evolved resistance to key bacteriophages could be responsible for some of the group-specific changes in surface-exposed FhuA loops. We recently found that Yersinia leucine-rich repeat genes had frequent mutations that were constrained to maintain protein activity and overall structure (36). Instead of random nucleotide substitutions, the amino acid codons tended to mutate with maximum parsimony (i.e., in the most straightforward and simplest way).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of random nucleotide substitutions, the amino acid codons tended to mutate with maximum parsimony (i.e., in the most straightforward and simplest way). Therefore, the observed mutations at the peptide level often showed predictable patterns rather than total irregularity (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation